The Impact of National Culture on International Business Negotiations - Analysis of the German and Finnish Negotiation Styles - Daniel Johannes, Kopp (My University, 2004)
The main objective of this thesis is the analysis of the German and Finnish business negotiation styles with respect to both countries’ national culture by using a twelve-dimensional framework. Further the aim is to examine the influence of the gender of managers and their age on the business negotiation style aside from the pure impact of national culture. The theoretical framework reviews theories on cultural variability of Trompenaars, Hall and Hofstede. Further an overview on negotiation models will be provided, with increased consideration of the Weiss and Stripp framework as it will be used for the empirical research. The link between Hofstede’s theory and the Weiss and Stripp framework will be explained and assumptions for the negotiation styles of German and Finnish managers will be made. The empirical part was carried out by using a questionnaire which was originally created by Professor Bird and Professor Metcalf and extended by Professor Larimo. The results based on the answers to the questionnaire were found by doing a quantitative research. The findings of this study show that the assumptions on every dimension, which were solely based on Hofstede’s theory on national culture did not lead to the expected results. For both nations, not every of the twelve assumptions could been verified as other effects apart from the national culture seem to influence the business negotiation style; such as learning effects, age and gender of negotiators. Therefore this study suggests to take further variables apart from national culture into account when analyzing the business negotiation styles.
Keywords: National Culture; International Business Negotiation; Quantitative Research.; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|